Disinfection, germination and micropropagation in vitro of Apuleia leiocarpa (Vogel) Macbride - D. Fabris; T. Gerber; L. M. Sartoretto (Scientific Electronic Archives, 2016)
The present study aimed to establish the protocols for disinfestations, germination and in vitro micropropagation of grápia (Apuleia leiocarpa (Vogel) Macbride). To disinfestations and break seed dormancy, were tested three treatments, and inoculated into test tubes containing growing medium. As for variable germination were tested four medium of nutritious, MS, MS½, WPM, WPM ½. And, to introduce organogenesis, the growing medium used was WPM, supplemented with BAP, at concentrations of 0,0; 0,4; 0,8 ml/L, combined with ANA in the concentration of 0,05 ml/L. The explants used in this study were hypocotyls and cotyledons obtained from grapia seedling germinated in vitro, 30 days after inoculation in growing medium. The organogenesis induction was performed in WPM growing culture. The evaluated parameters in this study were the disinfestation and break dormancy, germination and organogenesis induction. The data were subjected to variance analysis and the by Tukey test, at 95% of probability. Treatment III showed to be more efficient for both aseptic and to break seed dormancy, providing 92% of germination and 2% of contamination. As for the in vitro germination, the WPM and WPM½ growing cultures were the most effective, favoring 100% of germination. For various formations of calluses and sprouts on hypocotyls explants, there was no significant difference between the tested BAP concentrations. However, it was observed in cotyledon explants that the best results occurred at concentrations of 0,8 ml and 0,4 ml of BAP and 0,05 ml of ANA.